2015
DOI: 10.1016/j.ntt.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term behavioral impairment following acute embryonic ethanol exposure in zebrafish

Abstract: BACKGROUND Developmental exposure to ethanol has long been known to cause persisting neurobehavioral impairment. However, the neural and behavioral mechanisms underlying these deficits and the importance of exposure timing are not well-characterized. Given the importance of timing and sequence in neurodevelopment it would be expected that alcohol intoxication at different developmental periods would result in distinct neurobehavioral consequences. METHODS Zebrafish embryos were exposed to ethanol (0%, 1%, 3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 60 publications
(72 reference statements)
5
36
0
Order By: Relevance
“…64 Carvan et al 52 found adult zebrafish that were exposed from 0 to 24 hpf to 0.06% and 0.18% ethanol took significantly more trial to predict the location of a food reward. However, Bailey et al 66 found that fish exposed to either 1% or 3% ethanol from either 8 to 10 hpf or 24 to 27 hpf did not have impaired spatial discrimination. Taken together, these results demonstrate that not only can zebrafish be used to model the learning impairments of FASD but also to show the variability of embryonic ethanol exposure.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 98%
See 2 more Smart Citations
“…64 Carvan et al 52 found adult zebrafish that were exposed from 0 to 24 hpf to 0.06% and 0.18% ethanol took significantly more trial to predict the location of a food reward. However, Bailey et al 66 found that fish exposed to either 1% or 3% ethanol from either 8 to 10 hpf or 24 to 27 hpf did not have impaired spatial discrimination. Taken together, these results demonstrate that not only can zebrafish be used to model the learning impairments of FASD but also to show the variability of embryonic ethanol exposure.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 98%
“…60,66,67 Parker et al 60 reported that exposure to 0.12% ethanol from 48 to 216 hpf caused adult zebrafish to spend significantly more time at the bottom of the tank compared to untreated controls. This behavior is interpreted as elevated anxiety.…”
Section: Zebrafish Models Of Fasdmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish embryos exposed to ethanol have been used as models of fetal alcohol spectrum disorders, which result from maternal alcohol consumption during pregnancy (Table 1C). Zebrafish fetal alcohol spectrum disorders models have been used to understand the effects of prenatal alcohol exposure on behavior (Bailey et al 2015; Fernandes et al 2015), to gain an understanding of affected signaling pathways (Pappalardo-Carter et al 2013; C Zhang et al 2014; Zhang et al 2015), and to understand associated retinal tissue defects (Muralidharan et al 2014). Zebrafish have also been used to understand human obesity, which can have its cause rooted in multiple factors, including genetics and lifestyle.…”
Section: Zfin As a Resource For Zebrafish Translational Researchmentioning
confidence: 99%
“…Fernandes et al, 2014; Bailey et al, 2015; and for a review see Cole et al, 2012 or Ali et al, 2011). However, the literature describing the acute effects of ethanol exposure during adolescence or adulthood on learning and memory in zebrafish is more modest.…”
Section: Cognitive Effects Of Psychoactive Drugs In Zebrafishmentioning
confidence: 99%